Salivary gland tumours: a retrospective study at a tertiary care centre in South India - Swarnkar, Neha; Venkataraman, Srinivasan; Saravanam, Prasanna Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Salivary gland tumors are morphologically and histologically diverse group of lesions and their frequency varies in several parts of the world. Better understanding of these tumours will help in assessing the behaviour and outcomes of lesions of this region. The aim of this study was to analyse the charactertistics of different tumours occurring in the salivary gland in a tertiary care centre in South India. Methods: A retrospective study was conducted of salivary gland tumors diagnosed from the year 2015 to 2020. Patient age and gender, tumor site and frequency, histopathological diagnosis were evaluated and analysed. Results: A total of 36 salivary gland tumor cases was identified, 30 (87.3%) of which were classified as benign and 6 (12.7%) as malignant. Most tumors occurred in the parotid gland (81.3%). Pleomorphic adenoma was the most common tumor in 23 patients (63.8%), followed by warthins tumour. The tumors occurred more often in women than men. Conclusion: The results of the present study reinforce prevalence of salivary gland tumours. The parotid gland is the most common location and pleomorphic adenoma are the most frequent lesions. The malignant tumors also can occur in these glands and good clinical suspicion is necessary.